Photonic Crystals based Biosensors in Various Biomolecules Applications - Eunike Friska Defvi; Lita Rahmasari (Universitas Negeri Semarang, 2023)
Over the past decades, photonic crystals have emerged as interesting photonic structures. It plays a vital role in many fields of optical communication, biomedical sensing, and other applications due to its compactness, high sensitivity, high selectivity, fast responsiveness, etc. Strong light confinement in photonic crystals and adjustment of its geometrical parameters have led to the emergence of photonic crystal biosensors. Biosensors are extensively employed for diagnosing a broad array of diseases and disorders in clinical settings worldwide. Photonics crystal-based biosensor is one of the solutions to detect various diseases. By using literature review method, this paper aims to explore applications of photonic crystal-based biosensors to encounter the sensitivity of various biomolecules for cancer, malaria, and blood components detection.